2016
DOI: 10.1038/srep31298
|View full text |Cite
|
Sign up to set email alerts
|

Huaier restrains proliferative and invasive potential of human hepatoma SKHEP-1 cells partially through decreased Lamin B1 and elevated NOV

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cause of malignancy-related mortality worldwide. It is urgently needed to develop potential drugs with good efficacy and low toxicity for HCC treatment. The anti-tumor effect of Traditional Chinese Medicine (TCM) has received increasing attention worldwide. Trametes robiniophila Murr. (Huaier) has been used in TCM for approximately 1,600 years. Clinically, Huaier has satisfactory therapeutic effects in cancer treatment, especially in HCC. However, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…(Huaier) is a medicinal fungus that has been applied for disease treatment for more than 1600 years in China. Numerous studies have shown that Huaier exhibits good clinical efficacy in the treatment of liver cancer, gastric cancer, prostate cancer, colon cancer, breast cancer, and lung cancer (1)(2)(3)(4). There is evidence that some polysaccharides of Huaier aqueous extract show anti-tumor and immunomodulatory activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Huaier) is a medicinal fungus that has been applied for disease treatment for more than 1600 years in China. Numerous studies have shown that Huaier exhibits good clinical efficacy in the treatment of liver cancer, gastric cancer, prostate cancer, colon cancer, breast cancer, and lung cancer (1)(2)(3)(4). There is evidence that some polysaccharides of Huaier aqueous extract show anti-tumor and immunomodulatory activities.…”
mentioning
confidence: 99%
“…We demonstrated that the supernatants from murine macrophage-like RAW264.7 cells treated with TPG-1 showed dramatic cytotoxicity to human hepatoma HepG2 and SK-HEP-1 cells. Moreover, TPG-1 promoted the secretion of NO, 4 tumor necrosis factor ␣ (TNF␣), and interleukin-6 (IL-6) through TLR4-dependent activation of NF-B and MAPK signaling pathways in murine macrophage-like RAW264.7 cells. Furthermore, TPG-1 treatment significantly blunted the tumorigenic ability of HepG2 or H22 cells likely partially through facilitating the infiltration of leukocytes into tumors in mice.…”
mentioning
confidence: 99%
“…Moreover, Lamin B1 positively regulates the proliferation and invasion of pancreatic cancer cells (25). Our previous study revealed that as a pro-oncogenic gene, Lamin B1 was dramatically decreased in human hepatoma SKHEP-1 cells exposed to Huaier (10). Intriguingly, qRT-PCR and western blot analysis demonstrated that Huaier aqueous extract significantly inhibited the mRNA and protein levels of Lamin B1 in PC3 cells in a dose-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…In vitro scratch assay. The scratch assay was performed as described previously (10,18). In brief, PC3 cells were seeded into 12-well plates with complete medium.…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation